Social democracy in the making: political and religious roots of European socialism - Dorrien, Gary J. (Yale University Press, 2019)
Christian socialism in the making of social democracy -- British origins: Anglican socialism, early Marxism, and Fabian collectivism -- German social democracy: Marxism as theory and politics -- Germanic political theology: social democracy as theology --British breakthrough: guild socialist visions and social democratic realities -- Democratic socialism as pluralistic social democracy